Participatory Empowerment Communication in Community- Based Social Welfare - Prawira, R Yogie; Maulida, Hindina (Communicare : Journal of Communication Studies, 2025)
Community-Based Social Welfare (WKSBM) serves as a mechanism to address social issues at the grassroots level through active community participation. This initiative aims to foster a sense of responsibility, enabling individuals and communities to identify and develop their potential and creativity. Communication is essential in the empowerment process, as communication activities may not always proceed smoothly or yield the desired outcomes. This study seeks to examine the participatory empowerment communication strategy within the Community-Based Social Welfare Program (WKSBM) in Magelang City. The research employed a case study methodology, with data collected through in- depth interviews, observations, and document studies. Research participants included representatives from social services, social workers, community-based social welfare forums (WKSBM), sub-districts, and the community. The research data were analyzed through three stages: data reduction, data display, and conclusion drawing. The study's findings indicate that the participatory empowerment communication strategy encompasses several communication elements: 1) multiple actors in WKSBM empowerment, including the Magelang City Social Service, Magelang City Social Workers, Villages, and WKSBM Administrators; 2) messages conveyed both verbally and non-verbally, with language style and usage tailored to the audience; 3) media utilized, such as face- to-face interactions or WhatsApp; 4) the audience, comprising the general public starting from the neighbourhood level (RT/RW); and 5) the effect, evidenced by funds collected during the Covid-19 pandemic for vulnerable communities.